2019
DOI: 10.1016/j.cplett.2019.01.038
|View full text |Cite
|
Sign up to set email alerts
|

First detection of a key intermediate in the oxidation of fuel + NO systems: HONO

Abstract: This paper reports the first online gas phase detection of absolute concentrations of HONO under engine relevant conditions, during the oxidation of an alkane in the presence of NO x. The detection was achieved at laboratory scale thanks to the coupling of a jet-stirred reactor to a continuous-wave Cavity Ring-Down Spectroscopy cell. The evidence of the formation of HONO was obtained by comparing measured cw-CRDS spectra with a literature one. The formation of HONO was simultaneously observed with the appearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…However, for gasoline vehicles, the correlations between HONO and NOx emissions as well as HONO and NO 2 emissions are both poor (Figure S10). This might be attributable to the difference in the gas compositions of the exhausts of gasoline and diesel vehicles, such as carbonyl compounds, suggesting that the gas composition could be an important factor influencing the HONO emissions. ,, Therefore, although the ER HONO/NOx is widely used to estimate the HONO emissions from vehicles when HONO emission factors are not available, the low correlations between HONO and NOx found in this study indicated that such a proxy may bring high uncertainties in estimating the HONO emissions from the vehicles.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, for gasoline vehicles, the correlations between HONO and NOx emissions as well as HONO and NO 2 emissions are both poor (Figure S10). This might be attributable to the difference in the gas compositions of the exhausts of gasoline and diesel vehicles, such as carbonyl compounds, suggesting that the gas composition could be an important factor influencing the HONO emissions. ,, Therefore, although the ER HONO/NOx is widely used to estimate the HONO emissions from vehicles when HONO emission factors are not available, the low correlations between HONO and NOx found in this study indicated that such a proxy may bring high uncertainties in estimating the HONO emissions from the vehicles.…”
Section: Resultsmentioning
confidence: 80%
“…As ECE has higher frequencies of accelerations and decelerations, vehicles under the same emission control standard generally have higher HONO emissions for ECE driving cycles than those for the SSM cycles. This is probably because frequent speed changes can lead to incomplete combustion in the engine and promote the HONO formation from NO 2 and intermediate species such as HO 2 , CH 2 O, and CH 3 O, 19,35 indicating that the HONO emissions are sensitive to driving conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When its initial mole fraction is 500 ppm, NO starts to be consumed at 625 K; meanwhile, the mole fraction of NO2 increases sharply to reach approximately 300 ppm. Above 650 K, NO is fully consumed, and the amount of NO2 continues gradually increasing until 750 K. Concerning HONO, for which the quantification procedure under oxidation process was demonstrated elsewhere [45] its produced mole fraction is nearly 100 ppm at a temperature of 650 K. The HONO mole fraction also increases until the temperature is 725 K. After that, it decays as the temperature further increases. When NO2 (400 ppm) is added as a reactant, the onset temperature for its consumption is approximately 575 K, which is consistent with that of neat n-pentane as is shown in Figure 2.…”
Section: Oxidation Of Neat N-pentane: the Effect Of Different Bath Gasesmentioning
confidence: 99%
“…It was found that HONO signals were below the estimated/calculated detection limit (3 ppm) [44]. More recently, HONO signals were successfully identified and quantified during n-pentane JSR oxidation in the presence of NO [45].…”
Section: Introductionmentioning
confidence: 99%
“…It was already used in previous studies to quantify intermediates like hydrogen peroxide and HONO during the oxidation of fuels. 42,43 Ammonia has strong absorption lines in the wavenumber range 6637-6643 cm −1 , making the quantification accurate and providing a good sensibility. Fig.…”
Section: View Article Onlinementioning
confidence: 99%